Spotted Wing Drosophila New in Florida Berry Culture - James F. Price; Curtis A. Nagle (EDIS)
ENY857, a 3-page illustrated fact sheet by James F. Price and Curtis A. Nagle, describes this pest of strawberry, blueberry, raspberry and other thin-skinned fruit that was discovered in Hillsborough County in August 2009, and which strawberry growers should be prepared to encounter in winter 2010. It describes possible tactics for management. Includes references and a table of insecticides available for management of Drosophila spp. flies on strawberries in Florida. Published by the UF Department of Entomology and Nematology, October 2009.